THE INFLUENCE OF MILLENNIAL EMPLOYEE COMPETENCE IMPROVEMENT STRATEGIES ON BANK PERFORMANCE THROUGH HUMANITY LEARNING PROGRAMS - Permana, Irwan Triherda; Rahayu, Agus; Wibowo, Lili Adi; Setiawan, Yana; Yulianto, Erwin (International Journal of Artificial Intelligence Research, 2025)
The banking industry is currently facing the demands of the digitalization era, and the Millennial generation, as the majority of employees in the company, plays a crucial role in managing and making decisions for the continuity of the bank's business. In addition to the demands of digitalization, human resource skills play a strategic role in all positions within the company. For a bank to run smoothly, these human resource skills need to be accompanied by a learning strategy to improve the competency of millennial employees through a humanistic strategy implementation strategy so that the learning implementation can run smoothly and prudently. This study analyzes the Business Performance overview, which includes Digitalization Demands, Human Resource Skills, Millennial Employee Competency Improvement Strategies, and the Humanity Learning Program that influences it using a quantitative approach with descriptive and verification research types. The study population consisted of 544 regional offices, branches, and sub-branches of Bank BJB, which served as the analysis unit. Sampling used the Slovin method with 134 respondents. The research instrument used a questionnaire, and data analysis techniques to determine the correlative relationship in this study used the Covariance-Based Structure Equation Model. The results of the study show that the Demand for Digitalization with the dominant dimension of Digitalization Trends, Human Resource Skills with the dominant dimension of Digital Skills, and Millennial Employee Competency Improvement Strategy with the dominant dimension of Millennial Competency Development mediated by the Humanity Learning Program with the dominant dimension of Talent Development Program, significantly influence the Bank's Business Performance.